2016
DOI: 10.1103/physrevlett.117.277201
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Evolution of Spin-, Valley-, and Layer-Polarized Excited Carriers in Inversion-Symmetric WSe2

Abstract: We report the spin-selective optical excitation of carriers in inversion-symmetric bulk samples of the transition metal dichalcogenide (TMDC) WSe 2 . Employing time-and angle-resolved photoelectron spectroscopy (trARPES) and complementary time-dependent density functional theory (TDDFT), we observe spin-, valley-, and layer-polarized excited state populations upon excitation with circularly polarized pump pulses, followed by ultrafast (< 100 fs) scattering of carriers towards the global minimum of the conducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
155
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(169 citation statements)
references
References 37 publications
14
155
0
Order By: Relevance
“…The reason for such agreement is related to the surface sensibility of ARPES experiments. 9 In fact, scattering prevents photoelectrons to be ejected from the lower lying layers of the material and effectively only the topmost layers at the surface contribute to the spectrum. By comparing this spectrum to the experiments reported in Refs.…”
Section: Wse2mentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for such agreement is related to the surface sensibility of ARPES experiments. 9 In fact, scattering prevents photoelectrons to be ejected from the lower lying layers of the material and effectively only the topmost layers at the surface contribute to the spectrum. By comparing this spectrum to the experiments reported in Refs.…”
Section: Wse2mentioning
confidence: 99%
“…Time-resolved ARPES (tARPES) unlocks the time degree of freedom to study non-equilibrium dynamic of solids at the natural time scale of electronic excitations and relaxations [5][6][7][8][9] . Resolving the spin polarization of photoelectrons with spin ARPES (sARPES) provides additional information on the spin character of the sample [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…[71][72][73] As a more accurate alternative, one would turn to timeresolved-ARPES (trARPES) experiments, in which circularly-polarized pump pulses are used to access excited states. 74 Chemical engineering of the Rashba-Dresselhaus effects and SOC is possible through metal substitution (Pb, Sn, Ge). The ARIPES technique may provide a nice solution to probe the induced changes in the conduction band.…”
Section: Characterization Of Rashba and Dresselhaus Couplingsmentioning
confidence: 99%
“…The linearly polarized pump pulses create electronic excitations in the K and K' valleys of the conduction band. Time-and angle-resolved photoemission spectroscopy studies have shown that carriers scatter from the K valleys to the global minimum of the conduction band (the Σ valleys) within less than 100 fs [17,25]. Electron relaxation in multilayer WSe 2 at times larger than 100 fs is thus dominated by the phononmediated relaxation of electrons to the bottom of the conduction band within the Σ valleys.…”
mentioning
confidence: 99%
“…While time-and angle-resolved photoemission spectroscopy provides this level of detail for electron dynamics, see, for instance, Refs. [16,17], techniques for studying ultrafast structural dynamics have not yet reached the equivalent level of resolution. Recently, the investigation of the time-and momentum-resolved phonon population has been demonstrated with ultrafast x-ray and electron diffraction [18][19][20][21].…”
mentioning
confidence: 99%